Adherence is a key factor for interpreting the results of exercise interventions. (December 2021) - Nagpal, Taniya S.; Mottola, Michelle F.; Barakat, Ruben; Prapavessis, Harry
Abstract: Adherence may be an important factor to consider when interpreting the results of an exercise intervention. This article will discuss the importance of measuring and reporting adherence to exercise interventions that are designed to improve targeted health outcomes. Additionally, we will propose and describe a universal method to measure and report adherence to exercise interventions.